Acidosis Potentiates the Host Proinflammatory Interleukin-1β Response to Pseudomonas aeruginosa Infection - Torres, Iviana M. (Infect Immun, 2014)
Infection by Pseudomonas aeruginosa, and bacteria in general, frequently promotes acidification of the local microenvironment, and this is reinforced by pulmonary exertion and exacerbation. However, the consequence of an acidic environment on the host inflammatory response to P. aeruginosa infection is poorly understood. Here we report that the pivotal cellular and host proinflammatory interleukin-1β (IL-1β) response, which enables host clearance of the infection but can produce collateral inflammatory damage, is increased in response to P. aeruginosa infection within an acidic environment. Synergistic mechanisms that promote increased IL-1β release in response to P. aeruginosa infection in an acidic environment are increased pro-IL-1β induction and increased caspase-1 activity, the latter being dependent upon a functional type III secretion system of the bacteria and the NLRC4 inflammasome of the host. Using an in vivo peritonitis model, we have validated that the IL-1β inflammatory response is increased in mice in response to P. aeruginosa infection within an acidic microenvironment. These data reveal novel insights into the regulation and exacerbation of inflammatory responses to P. aeruginosa.